Unlocking Egypt’s Potential for Poverty Reduction and Inclusive Growth : Egypt Systematic Country Diagnostic Update - World Bank (World Bank, Washington, DC, 2021)
Systematic Country Diagnostics (SCDs) analyze the most critical constraints and opportunities to ending extreme poverty and promoting shared prosperity in a sustainable manner. The first SCD for Egypt was published in 2015. A lot has happened since then, so this SCD Update takes advantage of a longer stretch of reforms and newer data up to 2019 to identify and again assess the set of priorities through which Egypt can most effectively and sustainably achieve the goals of poverty reduction and shared prosperity.